PEMBERDAYAAN PELAKU USAHA BORDIR SKALA MIKRO DI KECAMATAN BANGIL KABUPATEN PASURUAN PROVINSI JAWA TIMUR - David Mayor; Agus Zakaria (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2019)
Empowerment of Micro Scale Embroidery Businessmen in Bangil District, Pasuruan Regency, East Java Province. There are still many micro-embroidery entrepreneurs in Pasuruan Regency who have not prospered their lives. Influenced by several factors that are interrelated with each other, resulting in the condition of some micro-embroidery business actors in Bangil Sub-District less able to develop and even threatened to decline. This study aims to describe the condition of the embroidery business in Bangil District, Pasuruan Regency. The method used in this study is descriptive qualitative. Data was collected by observation techniques focused on case study activities in Bangil District as an embroidery center in Pasuruan Regency. Equipped with interviews and documentation studies, the results show that the empowerment of micro-scale embroidery entrepreneurs in Bangil District is good. It still needs to be maximized. The Satrya Emas Program (Maslahat Economic Service Strategy) is the key to the success of MSME empowerment in Pasuruan Regency. This program is the development of the concept of Business Development Services (BDS) or a kind of economic clinic for Micro, Small and Medium Enterprises which is regulated in Regent Regulation number 13 of 2016. Keywords: empowerment, micro business, embroidery, bangil.